The Influence of School Climate on the Pedagogical Competence of Elementary School Teachers - Susilo Adi Saputro; Nur Khoiri; Lilik Ariyanto (Journal of Educational Sciences, 2026)
The background of this research is based on the importance of a conducive school climate in supporting teachers' pedagogical competence. This study aims to analyze the influence of school climate on the pedagogical competence of elementary school teachers in Gayamsari District, Semarang City. This study uses a quantitative approach with a correlational design. The study population consisted of 202 elementary school teachers, with a sample of 135 teachers selected using a proportional random sampling method. Data was collected through a Likert scale questionnaire that has been tested for validity and reliability. Simple linear regression analysis shows that school climate has a positive influence on teachers' pedagogical competence with a correlation coefficient of 0.322, indicating a weak influence between school climate and teachers' pedagogical competence. The coefficient of determination is 10.4%, indicating a large contribution of school climate to teachers' pedagogical competence. These findings indicate that school climate has a contribution in supporting the development of teachers' pedagogical competence, but it is not the only determining factor. Therefore, efforts to improve teachers' pedagogical competence need to be carried out comprehensively by integrating improvements in school climate and strategies for continuous teacher professional development.